Management of Quasi-Equivalent Concepts in Ontologies - Nesterova, Anna (2021)
Within the current master thesis, the author intended to analyze relevant topics and relevant methods to get an overview of the matching techniques that can be applied in the case of quasi-equivalent concepts. Analysis includes the current state of existing ontologies and concrete cases of the quasi-equivalent concept merging decision problems. The aim of this thesis project is to formulate tentative guidelines for making decisions in the case of quasi-equivalent concepts. Another goal was to obtain the feedback from ontology engineers on the challenge of quasi-equivalent concepts and how the decision can be handled. The outcome of the feedback has been analyzed to support the decision process.